1989
DOI: 10.1037/0022-0663.81.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Development of efficient arithmetic computation.

Abstract: The developing efficiency of simple arithmetic computations using dual reaction-time (RT) tasks was studied. The primary task of true-false verification of 2-term addition problems and the secondary task of auditory probe detection provided measures of the processing demands of encoding, computation, comparison, decision, and response stages of the addition process. Developmental shifts in the efficiency with which 2nd, 4th, and 6th graders and college adults computed answers to these problems were found. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…According to , arithmetic skill can be viewed on a continuum from novice to expert, with high-skill subjects retrieving arithmetic facts more frequently and more efficiently than lowskill subjects (see also Ashcraft, Donley, Halas, & Vakali, 1992;Kaye, 1986;Kaye, deWinstanley, Chen, & Bonnefil, 1989;LeFevre & Kulak, 1994); these effects were observed in the present study as well. Indeed, regression analyses showed that arithmetic skill was the only individual trait that was highly predictive both of use of a retrieval strategy and of strategy efficiency in both addition and multiplication problems.…”
Section: Arithmetic Skillsupporting
confidence: 74%
“…According to , arithmetic skill can be viewed on a continuum from novice to expert, with high-skill subjects retrieving arithmetic facts more frequently and more efficiently than lowskill subjects (see also Ashcraft, Donley, Halas, & Vakali, 1992;Kaye, 1986;Kaye, deWinstanley, Chen, & Bonnefil, 1989;LeFevre & Kulak, 1994); these effects were observed in the present study as well. Indeed, regression analyses showed that arithmetic skill was the only individual trait that was highly predictive both of use of a retrieval strategy and of strategy efficiency in both addition and multiplication problems.…”
Section: Arithmetic Skillsupporting
confidence: 74%
“…Because errors and latencies rose under such a load, Hitch and colleagues concluded that children's counting processes involve inner speech. The dual-task method was further used by Kaye, deWinstanley, Chen, and BonneWl (1989). In their study, second, fourth, and sixth graders veriWed simple addition problems while their working memories were loaded by means of a probe detection task.…”
Section: The Role Of Working Memory In Children's Arithmetic Strategymentioning
confidence: 99%
“…A third and Wnal shortcoming is that very few studies have investigated the role of working memory in normally achieving children (but see Adams & Hitch, 1997;Ashcraft & Fierman, 1982;Bull & Scerif, 2001;Geary, Bow-Thomas, Liu, & Siegler, 1996;Hecht, Torgesen, Wagner, & Rashotte, 2001;Kaye et al, 1989). Because we believe that it is important to know how the interaction between working memory and arithmetic performance progresses in normal development, the current study tested children without mathematical disabilities.…”
Section: The Role Of Working Memory In Children's Arithmetic Strategymentioning
confidence: 99%
“…It is also possible that some processes involved in verification (e.g., decision processes associated with pressing a button) were sped up as a result of additional time spent on computation processes. Kaye, deWinstanley, Chen, and Bonnefil (1989) reported evidence suggesting that raw latencies do not reflect how availability of memory resources contributes to verification during the solving of two-term additions (e.g., 34 + 56). Lack of available memory resources affected the computational phase in children and affected processes associated with comparison and decision stages in adults.…”
Section: -Accepted By Previous Editorial Teammentioning
confidence: 99%